Assessing organophosphate insecticide retention in muscle tissues of juvenile common carp fish under acute toxicity tests - Imtiyaz Qayoom; Masood Balkhi; Malik Mukhtar; Adnan Abubakr; Uzma Siddiqui; Sameena Khan; Asma Sherwani; Ishrat Jan; Riyazali Sayyed; Andrea Mastinu (Toxicology Reports, 2024)
Organophosphate insecticide spray poses potential threat of contamination of environmental components their accumulation in aquatic organisms. Although various physiological deficits associated with their exposure in fishes are documented, yet their retention in their edible muscle tissues has been poorly studied. In this context, the study was undertaken to ascertain the bioaccumulation of two organophosphate insecticide compounds (dimethoate and chlorpyrifos) in the muscles of juvenile Cyprinus carpio. The study could provide insight into the risks to human health associated with consuming contaminated fish flesh. The fishes exposed to various concentrations of dimethoate and chlorpyrifos in-vivo for 96 to ascertain the uptake and retention of these insecticides in the muscle. Results indicated that fish muscles accumulated the residues at all the concentrations with the recovery of 2.99% (0.032 ppm) of dimethoate exposed to LC50 concentrations. In contrast, the chlorpyrifos residues were found Below the Detection Level (BDL) in the fishes exposed to LC50 concentrations. The percentage bioaccumulation of dimethoate in fish muscle was 88.10%, and that of chlorpyrifos was BDL. The bio-concentration factor was dose-dependent and increased with increasing doses of both insecticides. The study invites attention to human health risk assessment in the regions where contaminated fish are consumed without scientific supervision.